Estimate for Euclidean parameters of a mixture of two symmetric distributions - Maiboroda, R. E.; Suhakova, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
A sample from a mixture of two symmetric distributions is observed. The considered distributions differ only by a shift. Estimates are constructed by the method of estimating equations for parameters of mean locations and concentrations (mixing probabilities) of both components. We obtain conditions for the asymptotic normality of these estimates. The greatest lower bounds for the coefficients of dispersion of the estimates are determined.